Mortality in retired coke oven plant workers. Issue 2 (February 1993) - Chau, N; Bertrand, J P; Mur, J M; Figueredo, A; Patris, A; Moulin, J J; Pham, Q T
Abstract : A previous study on 536 retired coke oven plant workers in Lorraine Collieries (France) reported an excess of deaths from lung cancer (standardised mortality ratio (SMR) = 251) compared with the French male population. Occupational exposures during working life were retraced for each subject, but the number of deaths during the observation period (1963-82) was small, and smoking habits were known only for dead subjects. In 1988, the cohort was re-examined (182 deaths occurred between 1963 and 1987) and smoking habits were determined for all the subjects. This study confirmed the excess of lung cancer (SMR = 238, p < 0.001). It showed an excess of mortality from all causes (SMR = 141, p < 0.001), overall cancers (SMR = 133, p < 0.05), and cardiovascular diseases (SMR = 133, p < 0.05). A significant excess of deaths was found for subjects who worked near the ovens for all causes (145, p < 0.01), lung cancer (SMR = 252, p < 0.01), colon cancer (SMR = 381, p < 0.05), and cardiovascular diseases (SMR = 155, p < 0.05). A significant excess mortality was also found from all causes (176, p < 0.05) and stomach cancer (SMR = 538, p < 0.01) in subjects who worked in byproducts, from lung cancer (SMR = 433, p < 0.001) in those in the workshops, and from cirrhosis of the liver and alcoholism (SMR = 360, p < 0.01) in those underground; but, due to small numbers, these figures were not robust. An excess of mortality from all causes (SMR = 163, p<001), lung cancer (SMR = 228, p<0.05) and cardiovascular diseases (SMR = 179, p<0.01) was shown also for non-exposed or slightly exposed subjects. The fact that, on the whole, mortality of various exposed groups was similar to that of non-exposed or slightly exposed workers may be explained in part by the selection at hiring and the healthy worker effect. As an increased risk of lung cancer was noted among subjects who worked in the old generations of plant compared with the other workers (although the relative risk was not significant) it is concluded that the role of occupational hazards could not be excluded.